1984
DOI: 10.1002/bjs.1800711012
|View full text |Cite
|
Sign up to set email alerts
|

What has happened to perforated peptic ulcer?

Abstract: The number of elective operations for chronic peptic ulceration has decreased substantially with the widespread use of H2-receptor antagonists. We have reviewed all cases of perforated peptic ulcer in Oxford over the last 18 years (1965-82) to see if a similar change in the incidence of this major complication of peptic ulceration has occurred. Since 1976 there has been a fall in the incidence of perforated peptic ulcer from 8.7 to 6.9 cases per 100 000 population per year. The male to female ratio decreased o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 17 publications
5
37
1
Order By: Relevance
“…2 It is common in a younger age group in the tropical countries (mean age in our study was 39.8 years) in comparison to the studies from West. [6][7][8] Male 69.9%, and female 30.1% were present in our series similar to other studies. 9 Perforation of the proximal part of the gastrointestinal tract were more common, 10 which is in contrast to the studies from western countries where perforations are common in the distal part.…”
Section: Discussionsupporting
confidence: 91%
“…2 It is common in a younger age group in the tropical countries (mean age in our study was 39.8 years) in comparison to the studies from West. [6][7][8] Male 69.9%, and female 30.1% were present in our series similar to other studies. 9 Perforation of the proximal part of the gastrointestinal tract were more common, 10 which is in contrast to the studies from western countries where perforations are common in the distal part.…”
Section: Discussionsupporting
confidence: 91%
“…Most commonly it affects the younger age group in the tropical countries (mean age in the present study group was 38.6 years) as compared to western world . [5][6][7] Most of the cases present late to the hospital with well-established generalized peritonitis having gross purulent or fecal contamination and varying degrees of septicemia. It is possible to make the diagnosis of peritonitis clinically in almost all the cases due to typical signs and symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Various authors [2, 3, 9, 16]report a decrease in elective surgery for GDPU, which they relate to the widespread use of drugs such as anti-H 2 and proton pump inhibitors over the last two decades. These drugs are very efficient for curing ulcer outbreaks but do not prevent ulcer recurrence if treatment is discontinued [17].…”
Section: Discussionmentioning
confidence: 99%
“…Since then various studies have implicated Helicobacter pylori in the pathogenesis of the disease [5, 6, 7], and the Consensus Conference held by the National Institute of Health in 1994 recommended that all patients with GDPU and H. pylori infection should be treated with antimicrobe therapy [8]. However, in the same period of time it was reported that the number of surgical procedures performed in patients with complicated GDPU has remained unchanged [9, 10, 11, 12]. We recently reported a significant decrease in the need of surgery for peptic pyloric stenosis, which is probably due to the influence of treatment with proton pump inhibitors and H. pylori antimicrobe therapy [13].…”
Section: Introductionmentioning
confidence: 99%